The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.rbce.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Análise dos gols do Campeonato Brasileiro de 2008 – Série A

Abstract: Resumo O objetivo deste artigo é quantificar e analisar a ocorrência de assistências, finalizações e pontos da baliza onde a bola entrou, para comparar a prevalência das variá-veis entre as equipes locais e visitantes. Os dados foram compostos por 1.035 gols, marcados em 380 jogos do Campeonato Brasileiro de 2008. Os gols foram analisados a partir de um campograma e de um modelo de divisão da trave. Os locais de assistência de bola em movimento que resultaram em gols foram de fora da área ao centro e fora da á… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
(9 reference statements)
2
1
0
1
Order By: Relevance
“…Our results demonstrate that the greatest number of goals were scored from the penalty area (mostly zones A and B), which is in line with the findings of several other researchers (Clemente et al, 2014;De Andrade et al, 2015;Palomino et al, 2000;Rodenas et al, 2020;Santos et al, 2016Santos et al, , 2017Santos et al, 2015;Tenga et al, 2010). However, there is moderate disparity between zones A and B, with more goals being scored from zone B.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results demonstrate that the greatest number of goals were scored from the penalty area (mostly zones A and B), which is in line with the findings of several other researchers (Clemente et al, 2014;De Andrade et al, 2015;Palomino et al, 2000;Rodenas et al, 2020;Santos et al, 2016Santos et al, , 2017Santos et al, 2015;Tenga et al, 2010). However, there is moderate disparity between zones A and B, with more goals being scored from zone B.…”
Section: Discussionsupporting
confidence: 92%
“…These results are expected considering that the greatest number of goals were obtained during offensive organizations as discussed in previous studies (Garratt et al, 2017). Of the 174 goals scored, 21 (12%) resulted from rebounds, which may indicate a lack of pressure from the opponent, as suggested in a study of the 2008 Brazilian Championship (De Andrade et al, 2015). This finding indirectly indicates lower levels of competitiveness and tactical organization.…”
Section: Discussionsupporting
confidence: 59%
“…This is in agreement with Hughes and Franks 9 , who conducted a study on the 1990 and 1994 World Cups and found that the most successful teams had significantly higher numbers of goal kicks after longer sequences of passes (more emphasis on ball possession). Andrade et al 22 analyzed 1,035 goals scored in 380 matches of the 2008 Brazilian National Championship -Premier Division, and found that only 1.5% of the goal assistance came from the defensive field, exclusively in dead ball situations. Anderson and Sally 23 verified that teams that used long distance passes most in the British Soccer League scored fewer goals and faced the threat of relegation at the end of the season.…”
Section: Discussionmentioning
confidence: 99%
“…A produção historiográfica levada a efeito por Luís Saia se intensificou na década de 1950, quando a questão urbana se torna fundamental em sua obra. No entanto, o arquiteto já havia publicado dois importantes artigos: "Os alpendres nas capelas brasileiras" (1939), e "Notas sobre a arquitetura rural paulista no segundo século" (1944), além de ter contribuído com o artigo de Mário de Andrade sobre a capela de Santo Antônio, publicado em 1937 (ANDRADE, 1937). Do total dos bens tombados durante a atuação de Luís Saia, 17 tombamentos foram realizados até o final da década de 1940.…”
Section: As Ações Preservacionistasunclassified